Navigating and negotiating information and support: Experiences of first‐time mothers. Issue 3 (22nd February 2018) - Aston, Megan; Price, Sheri; Monaghan, Joelle; Sim, Meaghan; Hunter, Andrea; Little, Victoria
Abstract : Aims and objectives: To examine how first‐time mothers in Nova Scotia identified and prioritised their own postpartum needs and where they went for information and support, inclusive of informal or formal programmes and services, social media, family and friends. Background: The early postpartum period is an exciting, yet stressful life experience for first‐time mothers. Mothers have often turned to families, friends and healthcare professionals for support and information; however, these social networks look differently today due to changes in institutional policies and postpartum healthcare practices, as well as the emergence of online resources and networks. There is currently limited understanding of how online resources have shifted mothers social networking practices and the degree to which programmes and resources are currently meeting the needs of mothers and families. Methods: Data were collected through focus group interviews in rural and urban Nova Scotia communities ( n  = 19) and online electronic interviews ( n  = 18). Data were analysed using feminist poststructuralism and discourse analysis to understand issues of inclusion and health equity for mothers and how relations of power were negotiated by first‐time mothers in their search for support and information. Results: Most participants were savvy as they critiqued, compared, navigated and negotiated advice and information from various sources, including health professionals, family, friends and online forums. However, they unanimously wanted face‐to‐face support with other mothers and healthcare professionals. Participants enacted their agency to critically analyse information and support to ensure it matched their own beliefs, values and practices. Conclusions: It is important to understand first‐time mothers' practices and need for face‐to‐face support, as well as a need for further research with more diverse or marginalised demographics of mothers.